Strategy for Stereocomplexation of Polylactide Using O/W Emulsion Blending and Applications as Composite Fillers, Drug Carriers, and Self-Nucleating Agents - Im, Seung Hyuk; Park, Su Jeong; Jung, Youngmee; Chung, Justin J.; Kim, Soo Hyun (American Chemical Society, 2020)
Biodegradable polymer polylactide (PLA) can form stereocomplex crystals through racemic blending between poly(L-lactide) (PLLA) and poly(D-lactide) (PDLA). This stereocomplexation could lead to substantially improved mechanical and physical strengths for PLA. Various methods for preparing stereocomplex PLA (sc-PLA) have been studied, e.g., solution blending, melt blending, and supercritical fluid (SCF) technology. However, current methods inevitably have various drawbacks including poor efficiency, usability, and low stereocomplexation reaction speeds. Thus, the aim of this study is to develop a novel strategy using oil-in-water (O/W) emulsion blending to overcome the current limitations of stereocomplexation. Our results indicate that the developed strategy can considerably improve the efficiency and accessibility of stereocomplex crystal formation compared to conventional methods such as solution blending and SCF technology. The O/W emulsion blending method exhibits a stereocomplexation efficiency of up to nearly 99%. Additionally, the sc-PLA produced by O/W emulsion blending can act as filler in PLA composites, leading to improvement of their mechanical properties. In addition, a cancer drug such as fluorouracil (5-FU) could be infiltrated into sc-PLA during stereocomplexation induced by O/W emulsion blending. Furthermore, sc-PLA with 5-FU prepared by the novel method could be added for ISN-polymerization in order to give both a nucleating effect and an anticancer effect. It suggests that sc-PLA prepared by our novel method could act as a stable carrier for secondary molecules as well as nucleating agents.
Keywords: ENANTIOMERIC POLY(LACTIC ACID)S; COMPRESSIVE STRENGTH; VASCULAR SCAFFOLDS; MELT; POLYMERIZATION; LACTIDE; CAST